"A lepra e a ordem": uma história da construção do hospital colônia Getúlio Vargas - Paraíba (1929-1941) - Nascimento, Emanoel Calixto do (2019)
This paper aims to discuss the processes that led to the construction of the Getúlio Vargas Colony Hospital in the village of Barreiras, present-day Bayeux-PB, to compulsorily contain every individual who had Hanseniase, a disease popularly known at the time as Leprosy. The time frame chosen for the research begins in 1929 and continues until 1941, the year of the inauguration of the colony hospital. From the late 1920s, the official newspaper of the state of Paraíba, the A União, began to carry news that concerned the creation of a leprosarium in the state. This journal was used as the main source of this research and throughout the period reported in this work, has been publishing news about the progress of the venture, demonstrating how the interests of doctors, politicians and society of the period, aimed at creating an anti-terrorism apparatus. - a leper in this state, as a method of protecting “healthy” society from leprosy, a disease of strong stigma that at the time had no cure and was a source of fear to the population. This paper also discusses how philanthropy through the the Sociedade de Assistência aos Lázaros e Defesa Contra a Lepra, acted actively in arranging funds that would be destined to the creation of a preventive for the reception of healthy children taken to the colony. During the writing of this dissertation, I dialogue with the perspectives approached by Michel Foucault (2014) about the methods of control and discipline within the institutions and also through the ideas of Erving Goffman (1987) about the “Total Institutions”. The research presents how disease and pacient were put on stage in and by the press to foster the creation of an institution to take care of these patients. It is concluded that the project of Hospital Colônia Getúlio Vargas, founded in 1941, was the result of a federal and state government action in conjunction with the media of the time, especially the A União newspaper, to build a local specializing in the containment and care of lepers in this state.